Restorative Justice is a Progressive Breakthrough in Resolving Criminal Law Problems - Asa, Agam Ibnu; Syamsuddin, Muhammad Mukhtasar; Zubaidi, Ahmad; Wahyudi, Agus (International Journal of Law Reconstruction, 2025)
The prevailing criminal law paradigm worldwide remains rooted in the penal system, where offenders are subjected to punitive measures, such as imprisonment, based on their level of guilt. This approach often prioritizes the punishment of the offender while neglecting the needs and rights of the victim. This study examines restorative justice as an alternative method of crime resolution, seeking to address the limitations of the conventional criminal justice system. Through qualitative research and a philosophical juridical approach, the study identifies the legal foundations of restorative justice in Indonesian criminal law, evaluates its challenges, and assesses its effectiveness in reducing judicial inequality and promoting social reconciliation. The findings highlight that restorative justice is reflected in Indonesia’s juvenile justice system, particularly under Law No. 11 of 2012, and is also integrated into the proposed Criminal Code Bill, specifically in Articles 116, 117, and 118. Key challenges to implementation include the retributive nature of the Indonesian legal system, limited understanding among law enforcement officials, and societal concerns over the perceived leniency of non-custodial sentences. However, restorative justice presents significant potential as a progressive solution for resolving criminal acts, contingent on strong commitment from all stakeholders and alignment with Indonesia's socio-cultural context and morality.